1998
DOI: 10.1001/archpsyc.55.9.816
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Depression With Cognitive Behavioral Therapy

Abstract: Background:Cognitive behavioral treatment (CBT) of residual symptoms after successful pharmacotherapy yielded a substantially lower relapse rate than did clinical management in patients with primary major depressive disorders. The aim of this study was to test the effectiveness of this approach in patients with recurrent depression (Ն3 episodes of depression).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
323
2
19

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 469 publications
(360 citation statements)
references
References 53 publications
16
323
2
19
Order By: Relevance
“…In addition, the inclusion criteria of eligible patients, such as previous interventions of these patients, in these trials were different as well. Two trials by Fava et al [46,49] implemented the intervention of CBT as described by Beck et al [60], while others respectively used their own manuals which were modified from that by Beck et al [60]. All the authors delivered CBT in face-to-face modality other than Holländare et al [52], who delivered it in the modules of internet communication and encrypted e-mails which largely decreased time of therapist.…”
Section: Cbtmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the inclusion criteria of eligible patients, such as previous interventions of these patients, in these trials were different as well. Two trials by Fava et al [46,49] implemented the intervention of CBT as described by Beck et al [60], while others respectively used their own manuals which were modified from that by Beck et al [60]. All the authors delivered CBT in face-to-face modality other than Holländare et al [52], who delivered it in the modules of internet communication and encrypted e-mails which largely decreased time of therapist.…”
Section: Cbtmentioning
confidence: 99%
“…Only one trial by [49] reported subjects with 3 or more previous MDD episodes. They found that compared to control, CBT had a preventive effect (HR:0.31, 95%CI:0.10-0.97).…”
Section: Cbt Vs Controlmentioning
confidence: 99%
“…Treatment with cognitive therapy resulted in a significant reduction in recurrence rates at 4 years (35% versus 70%) (Fava et al, 1998a). After 6 years of follow-up (Fava et al, 1998b), 10 of the patients in the cognitive therapy group (50%) and 15 of the patients in conventional treatment (75%) had suffered relapses; however, this difference was not statistically significant. When multiple recurrences were considered, the patients submitted to cognitive therapy had significantly fewer episodes and responded to the same antidepressant used in the basal episode of the study.…”
Section: Prevention Of Relapsesmentioning
confidence: 92%
“…Because of its high prevalence and resulting disability (major depression is classified as the second greatest cause of disability, adjusted for years of life, in developed countries) (Murray & Lopez, 1996). The concern in preventing recurrences of MDE is relevant and has been the target of research both with pharmacological treatment and psychotherapy (Antonuccio et al, 1995;Fava et al, 1996;Fava et al, 1998a;Fava et al, 1998b;Hollon et al, 2005).…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation